Comparative Study Between Karaman Score and Modified Alvarado Score for Predictability in Avoiding Negative Appendectomy in the Suspected Cases of Acute Appendicitis - Rooh Ali Ghumro, Sughra Parveen, Tanweer Ahmed, Kanwal Hanif, Asif Khowaja, Faraz, Kanwal Soomro (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the diagnostic accuracy between the Karaman score and the Modified Alvarado score for predictability in avoiding a negative appendectomy in suspected cases of acute appendicitis. Material and methods: This comparative study was done at the general surgery department of JPMC Karachi, from February 2022 to August 2022. All the patients diagnosed as the cases of acute appendicitis undergoing surgical treatment, aged more than 14 years and of either gender, were included. Both the Karaman and the Alvarado scoring systems were implemented in order to assign points to each of the study subjects. The Alvarado score is comprised of eight different parameters, while the Karama score only makes use of six different parameters. After evaluating the patient on both scores, the decision to perform surgery was primarily based on the surgeon’s clinical judgement after considering all clinical, laboratory, and radiological findings. Postoperative histopathology reports were collected, and the scores of both Alvarado and Karaman score were compared. Patients were operated and monitored throughout the stay in hospital up to discharge. Afterwards, for each score, sensitivity, specificity, and positive and negative predictive values were determined. All the data was collected via a study proforma, and SPSS version 26 was used for the data analysis. Results: In this study, 180 cases of appendicitis undergoing surgical treatment were studied, their mean age was 27.03 ± 10.12 years, and their mean BMI was 19.88 ± 3.43 kg/m2. Males accounted for 80.0% of all study participants. As per histological findings, acute appendicitis was found in 78.9% of the cases, 14.4% of the patients had gangrenous appendicitis, while 6.5% of the cases had a normal appendix. Histopathological evaluation was statistically significant according to the appendicitis identification by Karaman scoring system and Alvarado scoring system (p-0.001). Although both scoring systems showed almost similar diagnostic accuracy, the Karaman scoring system showed sensitivity (98%), specificity (75%), PPV (98%), NPV (75%), and accuracy (96%), while the Alvarado scoring system showed sensitivity (97%), specificity (58%), PPV (97%), NPV (63%), and accuracy (95%). Conclusion: In the study conclusion, the Karaman score and Alvarado scoring systems both were observed to be the good predictive to distinguishing acute appendicitis in avoiding the negative appendectomy. Both showed almost similar and high sensitivity and accuracy by taking histopathology is gold standard. Keywords: Appendicitis, Karaman score, Alvarado score, Accuracy